Effect of an early music intervention on emotional and neurodevelopmental outcomes of preterm infants at 12 and 24 months - Filippa, Manuela; Lordier, Lara; Lejeune, Fleur; De Almeida, Joana Sa; Hüppi, Petra Susan; Barcos-Munoz, Francisca; Monaci, Maria Grazia; Borradori-Tolsa, Cristina (Frontiers in Psychology, 2024)
Background. Few studies have found long-term effects of early musical environmental enrichment in the NICU on preterm infant's development. This study examines how early music enrichment affects emotional development and effortful control abilities in 12-and 24month-old very preterm (VPT) infants. Methods. 119 newborns were recruited, including 83 VPTs and 36 full-term (FT) infants. The VPT infants were randomly assigned to the music intervention (44 VPT-Music) or control (39 VPT-control) groups. VPT-Music infants listened specifically designed music intervention from the 33rd week of gestation until hospital discharge. At 12 and 24 months, children were clinically evaluated using the Bayley-III Scales of Infant and Toddler Development and the Laboratory Temperament Assessment Battery, and at 24 months, with 3 additional episodes of the Effortful Control Battery.Results and discussion. Our analysis showed that during a fear eliciting task, the VPT-Music group expressed lower level of fear reactivity and higher positive motor actions than VPTcontrols and FT infants. At 24 months, the VPT-music group had lower scores for negative motor actions in the joy task, compared to both VPT-control and FT groups. In addition, both FT and VPT-music had higher scores of sustained attention compared to VPT-controls, but the contrasts were not significant. No significant effects on mental, language and motor outcomes were identified and for all three dimensions of the ECBQ.Conclusions. The present study suggests that an early music intervention in the NICU might influence preterm children's emotional processing at 12 and 24 months. Limitations and suggestions for future research are highlighted.